Technical Efficiency Analysis Of Home Industry Kamang Crackers In Kenagarian Kamang Hilir Kamang Magek District, Agam Regency West Sumatra Province - Sari, Silvi Permata; Romdhon, Muhamad Mustopa; Utama, Satria Putra (Agroindustrial Journal, 2023)
Technical efficiency is the ability of an industry to use minimum total input to produce maximum output. This research aims to 1) Analyze the level of technical efficiency in the Kamang cracker home industry in Kamang Hilir Kenagarian, and 2) Analyze what factors influencing the level of technical efficiency in the Kamang cracker home industry in Kamang Hilir Kenagarian. This research was carried out deliberately in Kenagarian Kamang Hilir, Kamang Magek District, Agam Regency. Respondents in this study using the Slovin formula, totaling 51 Kamang cracker home industry entrepreneurs using a simple random sampling technique. Using primary and secondary data, while the data analysis used is qualitative descriptive analysis and the Cobb-Douglass production function method which is converted into logarithmic form, then data analysis uses Stochastic Frontier. The analysis results showed that the average level of technical efficiency was 0.5792, proving that the hypothesis in this research was proven correct. Can be concluded that the Kamang cracker home industry is technically efficient and the factors that influence technical efficiency are raw materials, salt, hours people work, age, number of family members while green onions, pertalite and gas fuel, education, business experience are not significant in the Kamang cracker home industry